Association Between C-Reactive Protein to Lymphocyte Ratio and Chronic Obstructive Pulmonary Disease: A Cross-Sectional Study - Ao T; Huang Y; Zhen P; Hu M (International Journal of COPD, 2025)
Ting Ao, Yingxiu Huang, Peng Zhen, Ming Hu Department of Infectious Diseases, Beijing Luhe Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Ming Hu, Department of Infectious Diseases, Beijing Luhe Hospital, Capital Medical University, No. 82, Xinhua South Road, Tongzhou District, Beijing, 101100, People’s Republic of China, Tel +86 13651328259, Email hmyx2012@sina.comBackground: The inflammatory response plays a critical role in the progression and prognosis of Chronic Obstructive Pulmonary Disease (COPD). The C-reactive protein to lymphocyte ratio (CLR) has emerged as a potential novel biomarker of systemic inflammation. Nevertheless, the association between CLR and COPD remains unclear. The objective of this study was to explore the possible connection between CLR and COPD.Methods: We conducted a retrospective study on 22,581 participants from the NHANES dataset (1999– 2010). To evaluate the relationship between CLR and COPD, logistic regression analysis, restricted cubic spline analysis, and threshold effect analysis were utilized. Furthermore, subgroup and sensitivity analyses were conducted to assess the robustness of the identified association.Results: Multivariate logistic regression models indicated that the ln-transformed CLR was significantly associated with an increased risk of COPD (OR: 1.14, 95% CI: 1.04– 1.25; P = 0.005). Compared to participants classified with the first tertile of ln-transformed CLR (T1), the risks of COPD for those in T2 and T3 were 1.03 and 1.33 times higher, respectively. An evident upward trend was noted with an increase in the ln-transformed CLR (P for trend =0.032). Furthermore, an inverse L-shaped association was identified between the ln-transformed CLR and the risk of COPD. The robustness and consistency of these findings were further confirmed by subgroup and sensitivity analyses.Conclusion: Increased CLR correlated with a heightened risk of developing COPD, exhibiting nonlinear patterns and threshold effects.Keywords: C-reactive protein to lymphocyte ratio, chronic obstructive pulmonary disease, inflammation, national health and nutrition examination survey